Beliefs Associated With Sunscreen Use Among Non-Hispanic White Older Adults. Issue 3 (May 2022) - Holman, Dawn M.; Glanz, Karen; Jordan, Amy; Bleakley, Amy; Dasari, Sabitha
ABSTRACT: This study examines beliefs about sunscreen use among non-Hispanic white adults aged 50 years or older using online survey data ( n = 237). Multiple logistic regression analyses were conducted to examine beliefs associated with sunscreen use, adjusted by age, gender, education, geographic location, and skin cancer risk score. Those who believed sunscreen use would prevent them from getting sunburned (odds ratio [ OR ] = 1.84) and those who believed that their romantic partners thought they should use sunscreen ( OR = 1.72) were more likely to report sunscreen use. Those who believed sunscreen use would "take too much time" were less likely to report sunscreen use ( OR = 0.65). These findings can inform future research and messaging efforts, including the evaluation of intervention approaches that highlight the immediate benefits of sunscreen use, address concerns about sunscreen use taking too much time, and tap into the potential influence that older adults may have on the sunscreen use of their romantic partners.